2021
DOI: 10.1108/inmr-11-2019-0142
|View full text |Cite
|
Sign up to set email alerts
|

R&D spending and patents: levers of national development

Abstract: Purpose The level of R&D spending of a country tends to increase the national patent rate and, in consequence, can collaborate with its economic development. However, there are a few empirical studies investigating this phenomenon by comparing countries from all over the globe. The purpose of this paper is to disassemble the sources of R&D spending and identify the role of national patent applications as a mediator in the relationship between R&D spending and national development. Design/methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…Little literature exists on the explicit comparison between public funding models for science vs. private funding models, though the analogy of industrial R&D exists. The association between private R&D expenditures and the number of patents is positive, while there is no association between governmental R&D expenditures and the number of patents (Paula & Silva, 2021). The major difference between private and governmental R&D is that private R&D is constrained by the need for the firm to be profitable, which usually leads to them addressing a consumer need.…”
Section: Science In the Real World: The Interface Of Science With The...mentioning
confidence: 99%
“…Little literature exists on the explicit comparison between public funding models for science vs. private funding models, though the analogy of industrial R&D exists. The association between private R&D expenditures and the number of patents is positive, while there is no association between governmental R&D expenditures and the number of patents (Paula & Silva, 2021). The major difference between private and governmental R&D is that private R&D is constrained by the need for the firm to be profitable, which usually leads to them addressing a consumer need.…”
Section: Science In the Real World: The Interface Of Science With The...mentioning
confidence: 99%
“…Os pesquisadores também têm se dedicado a investigar as perspectivas e os desafios da produção de bioetanol na Amazônia. Diferentes fontes de biomassa, como cana-de-açúcar, mandioca e milho, têm sido avaliadas quanto ao seu potencial para a produção de etanol, considerando aspectos como rendimento, viabilidade econômica e sustentabilidade ambiental (DUTTA et al, 2019;ORTIZ;LOBATO, 2020;PAULA;SILVA, 2021) Além disso, estudos têm se voltado para a produção de biogás na região amazônica, explorando a utilização de resíduos orgânicos, como resíduos agrícolas e de pecuária, para a geração de energia renovável. Essa abordagem contribui para a redução de resíduos e emissões de gases de efeito estufa, além de proporcionar benefícios socioeconômicos para as comunidades locais (KUSS et al, 2015).…”
Section: Fonte: Autores (2023)unclassified
“…Additionally, the investment in education and science has a more significant impact on countries' ecological situation, which guides and influences public policy [7]. Furthermore, empirical research findings from 35 countries indicated that R&D spending help to directly improve the national patent application, thus contributing to national development [8]. Hence, exploring not only some of the HDI indicators is essential, but also it is important to consider other indexes related to innovation.…”
Section: Introductionmentioning
confidence: 99%